2020
DOI: 10.21203/rs.3.rs-19863/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conscious sedation for the management of dental anxiety in third molar extraction surgery: a systematic review.

Abstract: Background: Dental anxiety is a condition associated with avoidance of dental treatment and increased medical and surgical risks. This systematic review aims to summarize available evidence on conscious sedation techniques used for the management of Dental anxiety in patients scheduled for third molar extraction surgery, to identify best approaches and knowledge gaps. Methods: A comprehensive search was conducted including MEDLINE/Pubmed, EMBASE, SCOPUS, clinicaltrials.gov and the Cochrane Database of Systemat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“…The question asked was 'Can you remember anything from the period between falling asleep and awakening?' GA, general anesthesia; MAC, monitored anesthesia care A systematic review of seventeen randomized clinical trials on conscious sedation techniques for third molar surgery found that, although findings were inconclusive about the role of conscious sedation for managing dental anxiety, six studies reported that conscious sedation was associated with an improvement of dental anxiety [10]. We emphasize the importance of adequately informing the patient about the procedure beforehand.…”
Section: Discussionmentioning
confidence: 94%
“…The question asked was 'Can you remember anything from the period between falling asleep and awakening?' GA, general anesthesia; MAC, monitored anesthesia care A systematic review of seventeen randomized clinical trials on conscious sedation techniques for third molar surgery found that, although findings were inconclusive about the role of conscious sedation for managing dental anxiety, six studies reported that conscious sedation was associated with an improvement of dental anxiety [10]. We emphasize the importance of adequately informing the patient about the procedure beforehand.…”
Section: Discussionmentioning
confidence: 94%
“…Além disso, vantagens são atribuídas a essa técnica por aumentar a satisfação do paciente e do operador, redução da dor pós cirúrgica, inibição do reflexo de vômito e redução da ansiedade do paciente. (Sivaramakrishnan, 2017;Benzoni, 2020;Melini, 2020).…”
Section: Ansiedade Dor E Sedação Consciente No Tratamento Odontológicounclassified
“…Many a time's anxiety can be managed either by non-pharmacological techniques like behavior therapy or desensitization. 1 Sometimes the patients are exposed to general anesthesia which neither a cost effective technique nor free from complications. This technique also improves the patient and surgeon satisfaction.…”
Section: Introductionmentioning
confidence: 99%